Evidence of ljungan virus specific antibodies in humans and rodents, Finland. Issue 11 (12th July 2013) - Jääskeläinen, Anne J.; Kolehmainen, Pekka; Voutilainen, Liina; Hauffe, Heidi C.; Kallio‐Kokko, Hannimari; Lappalainen, Maija; Tolf, Conny; Lindberg, A. Michael; Henttonen, Heikki; Vaheri, Antti; Tauriainen, Sisko; Vapalahti, Olli
Abstract Ljungan virus (LV, genus Parechovirus, family Picornaviridae) is considered currently to be a rodent‐borne virus. Despite suggested human disease associations, its zoonotic potential remains unclear. To date, LV antibody prevalence in both humans and rodents has not been studied. In this study, two different LV immunofluorescence assays (LV IFAs) were developed with LV genotypes 1 (LV strain 87‐012G) and 2 (LV strain 145SLG), and cross‐neutralization and ‐reaction studies were carried out with LV strain 145SLG. Finally, a panel of 37 Finnish sera was screened for anti‐LV antibodies using two different LV IFAs (LV 145SLG and LV 87‐012G) and a neutralization (NT) assay (LV 145SLG), and 50 samples from Myodes glareolus by LV IFA (LV 145SLG). The LV seroprevalence study showed 38% and 18% positivity in humans and M. glareolus, respectively. LV IFAs and NT assays were compared, and the results were in good agreement. The data are the first evidence of humans and rodents coming into contact with LV in Finland. Additional studies are required in order to acquire a better understanding of the prevalence, epidemiological patterns and possible disease association of LV infections. J Med. Virol. 85:2001–2008, 2013. © 2013 Wiley Periodicals, Inc.